2011
DOI: 10.4103/0971-9261.74516
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial cyst of the spleen

Abstract: This is a report of a case of epithelial cyst of the spleen in an 8-year-old boy. The cyst showed squamous metaplasia on histology. The risk of malignant transformation is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…1 Acomprehensive differential diagnosis of cystic lesions of the spleen includes parasitic echinococcal cyst, congenital cyst, intersplenic pancreatic pseudocyst, pseudocystarising from splenic trauma,necrotising infection, pyogenic splenic abscess, metastatic diseases and cystic lymphangioma or hemangioma. 2…”
Section: Introductionmentioning
confidence: 99%
“…1 Acomprehensive differential diagnosis of cystic lesions of the spleen includes parasitic echinococcal cyst, congenital cyst, intersplenic pancreatic pseudocyst, pseudocystarising from splenic trauma,necrotising infection, pyogenic splenic abscess, metastatic diseases and cystic lymphangioma or hemangioma. 2…”
Section: Introductionmentioning
confidence: 99%
“…Other hypotheses explaining the genesis of primary splenic epithelial cysts include epithelial cell metaplasia from adjacent structures or vascular endothelium from peritoneal inclusions and embryonic inclusion of epithelial cells from adjacent structures. 9 Although common in children and young adults, mesothelial cysts are rare in older people. 4 However, in this current case, the mesothelial cyst was observed in a 66-year-old woman and it was suspected that the increase in the size of the splenic lesion was due to fluid accumulation within a late activated mesothelial cyst.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant potential is unknown; however, there is a report of squamous cell carcinoma arising in an epithelioid cyst within the spleen. 6 Epithelial cysts in IPAS is rare with half of these reported incidentally detected. Zavras et al reviewed 36 patients and found the mean age of patients to be 46 years and slightly over half were female.…”
Section: Discussionmentioning
confidence: 99%